Efficacy of psychosocial interventions for pregnancy rates of infertile women undergoing in vitro fertilization: a systematic review and meta-analysis. (31st December 2023) - Ha, Ju-Young; Park, Hyo-Jin; Ban, Seon-Hwa
Abstract: Purpose: This study aimed to analyze the efficacy of psychosocial interventions for improving pregnancy rates in infertile women undergoing in vitro fertilization (IVF) treatment through a systematic review and meta-analysis. Methods: Twelve studies were included in the meta-analysis. To estimate the effect size, a meta-analysis of the studies was performed using RevMan 5.3. The possibility of publication bias was evaluated using funnel plots and Egger's method. Results: A statistically significant effect size (standardized mean difference [SMD] = 1.39; 95% confidence interval [CI] = 1.11–1.71; p  = 0.004; I 2 = 19%) was found for the 12 studies that investigated the effects of psychosocial interventions on clinical pregnancy rates. The psychosocial interventions that had a significant effect on pregnancy rates were mind-body interventions (SMD = 1.37; 95% CI = 1.01–1.85; p  = 0.040; I 2 = 0%) and cognitive behavioral therapy (SMD = 2.19; 95% CI = 1.17–4.13; p  = 0.010). Conclusions: The results suggest that psychosocial interventions affect pregnancy rates. Moreover, they indicate that mind-body interventions and cognitive behavioral therapy are beneficial for improving the pregnancy outcome in infertile women undergoing IVF.